From Identity to Diplomacy: Indonesia’s Moderate Islam and Afghanistan Peacebuilding under Jokowi (2017-2021) - Hidayat, Muhammad Chanif (Analisa: Journal of Social Science and Religion, 2025)
Indonesia has increasingly engaged in Afghanistan’s peacebuilding process, yet the specific mechanisms linking this engagement to the construction of state identity remain underexplored. This article analyzes why and how Indonesia constructs and projects moderate Islamic identity to shape its foreign policy in Afghanistan under President Joko Widodo. Using the theory of constructivism and qualitative discourse analysis of officials statements, policy documents, publications from Indonesian Islamic civil society, and academic works, this article examines how environmental structures influence policy construction. The findings reveal that this identity is constructed as a response to both external structures, specifically the failure of militaristic approaches in Afghanistan and the proliferation of radical Islamic groups, and internal structures, namely domestic political polarization. Consequently, Indonesia projects moderate Islam as a “soft-power” instrument to offer alternative conflict resolution mechanisms in Afghanistan while concurrently reaffirming such identity and maintaining domestic consolidation. This article contributes to the existing body of knowledge by offering a nuanced understanding of how religious identity functions as a dual mechanism for international mediation and domestic stability in Muslim-majority democracies.